Oral Gel Loaded by Fluconazole‒Sesame Oil Nanotransfersomes: Development, Optimization, and Assessment of Antifungal Activity - Hala M. Alkhalidi; Khaled M. Hosny; Waleed Y. Rizg (MDPI AG, 2020)
Candidiasis is one of the frequently encountered opportunistic infections in the oral cavity and can be found in acute and chronic presentations. The study aimed to develop fluconazole-loaded sesame oil containing nanotransfersomes (FS-NTF) by the thin-layer evaporation technique to improve the local treatment of oral candidiasis. Optimization of the formulation was performed using the Box‒Behnken statistical design to determine the variable parameters that influence the vesicle size, entrapment efficiency, zone of inhibition, and ulcer index. Finally, the formulated FS-NTF was embedded within the hyaluronic acid‒based hydrogel (HA-FS-NTF). The rheological behavior of the optimized HA-FS-NTF was assessed and the thixotropic behavior with the pseudoplastic flow was recorded; this is desirable for an oral application. An in vitro release study revealed the rapid release of fluconazole from the HA-FS-NTF. This was significantly higher when compared with the fluconazole suspension and hyaluronic acid hydrogel containing fluconazole. Correspondingly, the ex vivo permeation was also found to be higher in HA-FS-NTF in sheep buccal mucosa (400 μg/cm2) when compared with the fluconazole suspension (122 μg/cm2) and hyaluronic acid hydrogel (294 μg/cm2). The optimized formulation had an inhibition zone of 14.33 ± 0.76 mm and enhanced antifungal efficacy for the ulcer index (0.67 ± 0.29) in immunocompromised animals with Candida infection; these findings were superior to those of other tested formulations. Hence, it can be summarized that fluconazole can effectively be delivered for the treatment of oral candidiasis when it is entrapped in a nanotransfersome carrier and embedded into cross-linked hyaluronic acid hydrogel.